Alternatively Activated Macrophages Are Host Cells for Chlamydia trachomatis and Reverse Anti-chlamydial Classically Activated Macrophages - Tietzel, Illya; Quayle, Alison J.; Carabeo, Rey A. (Frontiers in Microbiology, 2019)
The obligate intracellular pathogen Chlamydia trachomatis (Ctr) is the causative agent of the most common form of sexually transmitted disease in the USA. Genital infections with Chlamydia trachomatis can lead to inflammatory tissue damage followed by scarring and tissue remodeling during wound healing. Extensive scarring can lead to ectopic pregnancy or infertility. Classically activated macrophages (CA mϕ), with their anti-microbial effector mechanisms, are known to be involved in acute inflammatory processes during the course of infection. In contrast, alternatively activated macrophages (AA mϕ) contribute to tissue repair at sites of wound healing, and have reduced bactericidal functions. They are present during infection, and thus potentially can provide a growth niche for Chlamydia trachomatis during a course of infection. To address this question, macrophages derived from CD14-positive monocytes magnetically isolated from peripheral blood mononuclear cells were treated with interferon-γ or interleukin-4 to produce classically (CA mϕ) or alternatively activated macrophages (AA mϕ), respectively. Confocal microscopy of chlamydial inclusions and quantification of infectious yields revealed better pathogen growth and development in AA mϕ than CA mϕ, which correlated with the reduced expression of indoleamine 2,3-dioxygenase, a known anti-chlamydial effector of the host. Furthermore, AA mϕ stained strongly for transferrin receptor and secreted higher amounts of anti-inflammatory interleukin-10 compared to CA mϕ, characteristics that indicate its suitability as host to Chlamydia trachomatis. CA, AA, and resting mϕ were infected with Ctr serovar L2. The data suggest that IL-10 produced by infected AA mϕ attenuated the anti-chlamydial function of CA mϕ with growth recovery observed in infected CA mϕ in the presence of infected, but not mock-infected AA mϕ. This could be related to our observation that IL-10 treatment of infected CA mϕ promoted better chlamydial growth. Thus, in addition to serving as an additional niche, AA mϕ might also serve as a means to modulate the immediate environment by attenuating the anti-chlamydial functions of nearby CA mϕ in a manner that could involve IL-10 produced by infected AA mϕ.